The Influence of Product Strategy on Performance of Pepsi-Cola (Ea) Limited In Kenya - Arati, Simba Paul; Kisia, Rose; Koech, Caroline Sitienei (International Journal of Education and Research, 2021)
Marketing strategy is the fundamental goal of increasing sales and achieving a sustainable competitive advantage of a brand. Pepsi Cola (EA) Limited is an international food and beverage firm based in Kenya. However, despite several attempts to penetrate the local market, Pepsi has performed dismally and this is the ground on which this study is anchored. The study sought to establish the influence of product strategy on performance of Pepsi-Cola (EA) Limited in Kenya. The study was guided by the following theories: Porter’s Competitive Business Strategy Typology, Ansoff’s Product-Market Strategies and Contingency theory in explaining the relationship between marketing strategy and performance. Stratified random sampling was used to select a sample size of 150 respondents. Primary data was obtained through questionnaires and interview schedule. Both descriptive and inferential statistics were used in the analysis of data. Cronbach’s Alpha of 0.85 was used to test instrument reliability. The findings showed that product strategy explains 60.3% (R2 = 0.603) of the variation in performance of the organization. The findings also showed that the Product strategy was statistically significant: (F=225.103, p=0.000b ). Thus, the null hypothesis that product strategy has no significant influence on performance is rejected. The above R2 results show that, the model is stable for prediction. In conclusion, product strategy significantly affects performance of Pepsi Cola (EA) Limited. The study will be significant in the management of soft drink companies. Policy makers and regulators may use it. It can also form a basis for further research.